Growing Chlorella vulgaris on thermophilic anaerobic digestion swine manure for nutrient removal and biomass production. (November 2017) - Deng, Xiang-Yuan; Gao, Kun; Zhang, Ren-Chuan; Addy, Min; Lu, Qian; Ren, Hong-Yan; Chen, Paul; Liu, Yu-Huan; Ruan, Roger
Highlights: Chlorella vulgaris grew well on minimally diluted pretreated swine manure. Nutrients could be rapidly removed by C. vulgaris, particularly with bacteria. Chemical compositions in C. vulgaris changed with the culture conditions. The alga could be used as biodiesel feedstock if cultivated in PADSM. The algal biomass produced could be used as animal feed. Abstract: Liquid swine manure was subjected to thermophilic anaerobic digestion, ammonia stripping and centrifugation in order to increase the available carbon sources and decrease the ammonia concentration and turbidity. Chlorella vulgaris (UTEX 2714) was grown on minimally diluted (2×, 3× and 4×) autoclaved and non-autoclaved pretreated anaerobic digestion swine manure (PADSM) in a batch-culture system for 7 days. Results showed that C. vulgaris (UTEX 2714) grew best on 3× PADSM media, and effectively removed NH4 + -N, TN, TP and COD by 98.5–99.8%, 49.2–55.4%, 20.0–29.7%, 31.2–34.0% and 99.8–99.9%, 67.4–70.8%, 49.3–54.4%, 73.6–78.7% in differently diluted autoclaved and non-autoclaved PADSM, respectively. Results of chemical compositions indicated that contents of pigment, carbohydrate, protein and lipid in C. vulgaris (UTEX 2714) changed with the culture conditions. Moreover, its fatty acid profiles suggested that this alga could be used as animal feed if cultivated in autoclaved PADSM or as good-quality biodiesel feedstock if cultivated in non-autoclaved PADSM.